The Influence of Profit Growth, Leverage, and Profitability on Dividend Policy in State-Owned Enterprises Listed on the Indonesia Stock Exchange - Qurochman, Arief Nurdiannova (Enrichment : Journal of Management, 2022)
Dividend policy is part of management activities in paying rights to shareholders or investors. Determining the dividend policy is influenced by several things. This research is limited to several things or factors that are intended to determine their effect on dividend policy. Some of these factors include profit growth, leverage, and profitability. This study aims to determine the effect of profit growth, leverage, and profitability on dividend policy in State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange for the period 2018 to 2020. The population in this study is State-Owned Enterprises listed in one Indonesian Stock Exchange. Meanwhile, the sample selection used the purposive sampling method. The number of samples of companies used is 33 samples with 11 companies. The analysis technique used is multiple linear regression analysis to determine the relationship and influence between one dependent variable and several independent variables. Based on the results of research through t-test, it can be concluded that the company's profit growth has no effect on dividend policy, and this result is not in accordance with the hypothesis. Then, leverage also does not affect dividend policy, and this result is not in accordance with the hypothesis. And profitability also does not affect dividend policy, this result is not in accordance with the hypothesis. Meanwhile, the results of the study according to the f test concluded that profit growth, leverage, and profitability have a simultaneous effect on dividend policy.